Dirac Equation under Scalar, Vector, and Tensor Cornell Interactions - H. Hassanabadi; E. Maghsoodi; S. Zarrinkamar; H. Rahimov (Advances in High Energy Physics)
Spin and pseudospin symmetries of Dirac equation are solved under scalar, vector, and tensor interactions for arbitrary quantum number via the analytical ansatz approach. The spectrum of the system is numerically reported for typical values of the potential parameters.